2-3(x-7)=1

Simple and best practice solution for 2-3(x-7)=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2-3(x-7)=1 equation:


Simplifying
2 + -3(x + -7) = 1

Reorder the terms:
2 + -3(-7 + x) = 1
2 + (-7 * -3 + x * -3) = 1
2 + (21 + -3x) = 1

Combine like terms: 2 + 21 = 23
23 + -3x = 1

Solving
23 + -3x = 1

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-23' to each side of the equation.
23 + -23 + -3x = 1 + -23

Combine like terms: 23 + -23 = 0
0 + -3x = 1 + -23
-3x = 1 + -23

Combine like terms: 1 + -23 = -22
-3x = -22

Divide each side by '-3'.
x = 7.333333333

Simplifying
x = 7.333333333

See similar equations:

| 6(n-6)+7n=-140 | | x^1/3=4/3 | | 8x=-3+1 | | 2000+100h=1800+150h | | 1100+800+4z=700+300+7z | | 0.6x+4.3=3.4 | | 2y=-5y-24 | | (8x^4+3x^3-5)-(2x^2-6x+5)= | | 22-16=x | | 2(x+3)-1=3 | | 7/n=4/8 | | 6(4z-1)-3(z+6)=13(z+1) | | k-1/3=10 | | 4(-6)(-5)-2(-5)(2)= | | 2/5x-12=2 | | 6x+6y+6=0 | | 3*6-12/6 | | x-3/8=1x/3 | | 4x+6=4x-5 | | 6y+18=y+11 | | [[24]/[56]] | | 78=5t-7 | | -7(8x-7)+8(1+5x)=-23 | | 1-2x=3x-11 | | x-3/8=1-x/3 | | 3m+5=25 | | (20a^2b)/(4a^2b2) | | x(x)+3x-10=-6 | | 3x-(5)=4 | | 2a-3=-17 | | 4x+6=5*2x | | 6-x=4(3x-5) |

Equations solver categories